Sistema Automatizado em Python para Análise Técnica no Mercado Cambial - Malho, João Maria Caldeira Cardoso de Barros (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science